The Era Value and Management Innovation of Mass Cultural Activities - Yu, Suping (Journal of Theory and Practice of Management Science, 2023)
The development of mass cultural activities is mainly to meet people's spiritual needs, play a good promoting role in people's thinking, and have high contemporary value. With the rapid development of society, mass culture has become an indispensable part of people's lives. Reasonably carrying out mass cultural activities has profound historical significance. In this regard, the article outlines the main content of mass cultural activities, explores the era value of mass cultural activities, and puts forward several suggestions for management innovation of mass cultural activities.